Development and evaluation of carbamazepine fast dissolving tablets prepared with a complex by direct compression technique - Rao, N G Raghavendra; Patel, T; Gandhi, S (Asian Journal of Pharmaceutics (AJP), 2014)
The present study deals with the formulation of fast dissolving tablets of poorly soluble carbamazepine by the direct compression technique with Î²-cyclodextrin complexes using various super disintegrants like Indion-414, croscarmellose sodium, crospovidone and sodium starch glycolate. Carbamazepine is used to control different types of seizures in the treatment of epilepsy. Poor solubility in biological fluids is the major problem with this drug as also its poor bioavailability after oral administration.The rate of absorption and/or the extent of bioavailability for such a poor soluble drug is controlled by rate of dissolution in gastrointestinal fluids. Hence, to enhance the solubility of the drug, a complex of carbamazepine was prepared with Î²-cyclodextrin and this complex was compressed into tablets. The prepared tablets were evaluated for hardness, friability, drug content, weight variation, disintegrating time, wetting time, in vitro dissolution studies, etc. The prepared tablets were characterized by DSC, Fourier transform infrared spectroscopy (FTIR) and stability studies.The different formulations showed disintegration times between the ranges of 26.86 and 58.54 s. Drug release showed time between the ranges of 4 and 12 min. Among all the formulations, B8 showed 99.89% drug release within 4 min.Thus, B8 was considered as the best among the other formulations. No chemical interaction between the drug and the excipients was confirmed by DSC and FTIR studies. The stability study was conducted as per the ICH guidelines and the formulations were found to be stable, with insignificant changes in hardness, drug content and disintegration time.These results revealed that fast dissolving tablets of the poorly soluble drug, carbamazepine, showing enhanced dissolution and, hence, better patient compliance.